2016
DOI: 10.5507/ag.2016.009
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of static stretching of upper arm and forearm on the accuracy of free throws in basketball

Abstract: Background: Free throws are a very important element in modern basketball. There are many studies focused on different aspects ranging from variability in the mechanics of throwing at various skill levels to the influence of free throws on the results of games. Objective: Since the authors of the present study noticed that some players during a game apply static stretching of shooting arm as a preparation to perform the free throw, we wanted to question the justification of such procedure prior to the performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…However, through further analysis of professional and amateur player protocols via the focus groups, it was apparent that all but one of the amateur players took part in simple jogging activities as a preparatory activity whereas, the professional players incorporated a ball handling drill into their preparatory activity. The implementation of a ball handling drill, whilst simultaneously running at a submaximal pace, may have additive benefits to essential coordination patterns needed for a complex sport such as Rugby League, in additional to the desired effect of increasing core temperature (6,16,18,34,42). This is in accordance, with recommendations regarding the inclusion of skill based 'pulse raising' activities at the initiation of a warm-up protocol (20).…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…However, through further analysis of professional and amateur player protocols via the focus groups, it was apparent that all but one of the amateur players took part in simple jogging activities as a preparatory activity whereas, the professional players incorporated a ball handling drill into their preparatory activity. The implementation of a ball handling drill, whilst simultaneously running at a submaximal pace, may have additive benefits to essential coordination patterns needed for a complex sport such as Rugby League, in additional to the desired effect of increasing core temperature (6,16,18,34,42). This is in accordance, with recommendations regarding the inclusion of skill based 'pulse raising' activities at the initiation of a warm-up protocol (20).…”
Section: Discussionmentioning
confidence: 59%
“…Pringle et al (34) recorded significantly faster 40 m sprint times within elite Rugby League players performing a 16 min high intensity warm-up compared to when they performed a lower intensity 22 min warmup (5.26 s v 5.34 s, P = 0.033). The authors concluded, that a warm-up high in intensity and a maximum of sixteen min in duration will benefit the athlete due to an increase in core temperature and blood flow to the musculature (12,34,42). In addition, Frikha et al (14) discovered that an active warm-up of 15 min resulted in significantly greater peak power and mean power in the Wingate test compared to an active warm-up lasting 20 min.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations